The relationship of potential hazards towards safety impact at Malaysian floating storage facility - Md Fadzil, Salehuddin (2016)
Floating storage facility is increasingly becoming the preferred solution for new installation in offshore industry. The facility has the ability to handle changes of oil reservoir and process as well as offering storage and offloading at the same time. With the straight forward of building and conversion based on the ship building technology, the system will easily contribute to the potential hazard or risk that is difficult to quantify due to short of experience, if compared to shipping industry. This thesis gives an overview of the potential hazards during normal activity and the safety impact to personnel, asset and environment. The list of potential hazard is generated and compiled during reviewing of the literature from journals, conference proceedings, databases and guidelines related to offshore operation safety. The research study followed Risk Assessment approach by using Risk Matrix as a tool to measure the level of potential hazard. Survey data also analyzed through statistical method of analysis using SPSS. The tools from ANOVA One Way and T-Test were used to analyze further the significant differences of demographic facility towards potential hazards. Tool from Pearson Correlation is used to analyze the data for the relationshipof the potential hazard towards safety impact of the facility. The research study described the potential hazards mainly from marine activities that should be considered at the floating storage facility operated in Malaysia. The findings reported that the age of facility has significant difference for ship collision, from the perspective of facility’s demographic. The result also shows mooring system having significant difference for hull failure since the statistical finding is significant. For the level of hazard, it shows that on the first ranking is hydrocarbon release followed by occupational accident, ship collision and hull failure. The result shows positive, significant and yet low extent for the relationship of potential hazards towards safety impact of the facility. The findings from the collected experience-based and research survey data can be applied to facilitate the development of rationalized approaches for the top management in decision-making for the safety guideline, policy making and investment towards the floating storage facility.